A new mathematicalpProgramming aapproach to wind farm layout problem under multiple wake effects - Alabaş Uslu, Çiğdem; ÜLKÜ, İLAYDA (My University, 2019)
Wind farm layout optimization is one of the challenging problems in thefield of renewable energy. In thepresent study, a new nonlinear mathematical model for layout of wind turbines under multiple wakeeffects is proposed considering two objective functions separately: maximization of total power pro-duction and minimization of cost per power. To incorporate multiple wake effects into the proposedmodel, Jensen's wake decay model is employed. It was proven that the proposed model has totallyunimodularity property and according to this property, relaxation of binary decision variables relatedwith the wind turbine locations makes the model relatively simple to solve. Computational study revealsthat results of total power production and cost of power obtained from the proposed model outperformthat of the previous studies in the literature on a set of example cases and therefore, can be used to layoutmore productive wind farms.
Keywords: Rüzgar Çiftliği; Düzen Optimizasyonu; Uyanma Etkisi; Doğrusal Olmayan Programlama; Wind Farm; Layout Optimization; Wake Effect; Non-Linear Programming